Pedigree analysis of Hungarian sport horses - Posta, János; Komlósi, István; Mihók, Sándor (Animal welfare, Ethology and Housing Systems (AWETH), 2006)
Authors analysed the Hungarian Sport horse Studbook (contains ancestors at least 3 generations back) comprising a total of 11.286 individuals in order to ascertain the genetic structure of the breed and to evaluate its genetic variability. The numbers of founders based on this pedigree between birth years 1994 and 2003 were 2459 and 3222 individuals for stallions and mares, respectively. The effective numbers of founders were 376.3 and 512.9, respectively. Only 102 ancestors for stallions and 156 ancestors for mares were necessary to explain 50% of the genetic variability of the breed. One ancestor with the largest influence contributed 2.71% to the stallions’ and 2.15% to the mares’ genetic variability. There were 42 inbred individuals in the analysed population with mean inbreeding coefficient of 0.079.
Keywords: Hungarian Sporthorse; pedigree analysis; population structure; inbreeding; genetic variability